Immunotherapy With Egg Yolk Eimeria sp.-Specific Immunoglobulins in SPF Leghorn Chicks Elicits Successful Protection Against Eimeria tenella Infection - Juárez-Estrada, Marco A.; Tellez-Isaias, Guillermo; Sánchez-Godoy, Félix D.; Alonso-Morales, Rogelio A. (Frontiers in Veterinary Science, 2021)
AAvian coccidiosis is the first to most economically important parasite disease affecting poultry industries worldwide. Current prevention measures are largely based upon prophylactic chemotherapy supplemented by the application of live attenuated or wild-type parasite vaccines. However, the rising appearance of drug resistance, consumer´s concern for antibiotics use in poultry production and higher manufacturing cost of live vaccines has driven to adopt new technologies aimed at increasing animal health and production efficiency. Supplementing chickens with egg yolk Eimeria sp.-specific immunoglobulins can be a viable alternative to avoid severe outbreaks of the disease. Twelve-week-old SPF White Leghorn chickens were experimentally infected with a large dose of E. tenella. During the prepatent period, the birds were supplemented by oral gavage with 60 or 120 mg/bird of hyperimmune egg yolk Eimeria species-specific immunoglobulins Y (Supracox®, SC) on a daily basis. The animals were euthanized 7 days post-infection (PI) and their passive immune protection was evaluated. Birds treated with 120 mg/bird of SC showed more viability, increased body weight gain (BWG), a normal hematocrit level (HCT), reduced oocyst output per gram of feces (OPG) or cecal tissue (OPGC), and fewer cecal lesions compared to the untreated infected (UI) control group. Birds supplemented with 60 mg/bird of SC did not show any significant difference on BWG, HCT, OPG, OPGC, and cecal lesion score when compared with the UI group. An ELISA test of the SC showed a weak cross-reactivity of IgY toward two asexual zoite stages of E. tenella. Western blot analysis of the sporozoite with SC showed few antigens barely recognized, while more stained bands were detected in the merozoite (82, 60, 54, 40, 37.5, 30, and 13 kDa). Oral immunotherapy using egg yolk polyclonal IgYs against Eimeria sp. represents an effective and natural resource against severe E. tenella infection favoring the gradual withdrawal of the anticoccidial drugs and antibiotics.